PENGARUH RASIO KAS DAN RASIO CEPAT TERHADAP RENTABILITAS PADA KOPERASI SIMPAN PINJAM KOPDIT CU. PARDOMUAN PAKKAT CABANG PANDAN KABUPATEN TAPANULI TENGAH - Putri Angel Manalu; Zafril Abdi Nasution; Mansur Tanjung (Kapital Deli Sumatera, 2024)
The aim of this research is to determine the effect of the cash ratio and quick ratio on economic profitability at Koperas Savings and Loans Kopdit CU. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency draws the hypothesis that there is an influence of the cash ratio and quick ratio on profitability in the Kopdit CU Savings and Loans Cooperative. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency. The research results show that there is a positive relationship between the cash ratio and economic profitability and the quick ratio and economic profitability have a negative relationship in the Kopdit CU Savings and Loans Cooperative. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency are 0.226 and -0.077 respectively, so that when interpreted on a value scale they can be categorized as low positive and very low negative. The regression equation obtained is Y = 0.104 + 0.031X - 0.013X2 which shows the influence of the cash ratio and quick ratio on profitability. The t test shows that the hypothesis proposed is rejected as true, where the t count is 0.622 > 3.18245 for the cash ratio and the t count is -0.527 > -3.18245 for the quick ratio, where both ratios have a positive and negative effect on profitability which is not significant, which means does not necessarily increase or decrease by the respective regression coefficient/slop of 0.031 and -0.013 if the cash ratio and quick ratio variables are increased by one unit. Meanwhile, the coefficient of determination shows that the cash ratio and quick ratio only play a role of 16.7% in the profitability of the Kopdit CU Savings and Loans Cooperative. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency and the remaining 83.3% is influenced by other factors not included in the model. Keywords: Cash ratio, Profitability, Quick ratio